The Role of Verbal Representation Level in Decision Making under Uncertain Categorization - Yu.V. Sudorgina; T.N. Kotova; A.A. Kotov (Экспериментальная психология, 2022)
In this study we replicated (N=77) the effect of a decision making under uncertain categorization (i.e. basing the decision on a few categories simultaneously): when uncertainty was high, participants considered a few categories for a decision more often than when uncertainty was low, therefore, they made rational decisions more often [6]. Moreover, in Chen and colleagues’ study making rational decisions was not affected by the framing of category information. In the next part of our study (N=134) we further measured participants’ level of verbal representation using a scale from adapted version of Internal Representation Questionnaire [14] and found a relationship between framing of the task and rational decisions. Low level of verbal representation was followed by the greatest number of rational decisions in tasks with the choice frame, whereas middle and high levels of verbal representation were accompanied by the biggest number of rational decisions in tasks with the category frame. Since the level of verbal representation did not directly influence on the quantity of rational decisions, we proposed that verbal representation is connected with shifting attention either on categorical differences or on information about decision consequences during decision making process.